2022
DOI: 10.1093/bjsw/bcac211
|View full text |Cite
|
Sign up to set email alerts
|

The Connected Lives We Live: Autoethnographic Accounts of Disability, Mental Illness and Power

Abstract: In this article, we use a collaborative approach to autoethnography to explore experiences of power in relation to our identities as people with disabilities and/or mental illnesses. We draw on elements of Bronfenbrenner’s ecological systems framework to consider how we enact our own power or struggle against systemic power in making meaning of our lives. As a team of lived experience researchers we wrote, shared and thematically analysed a series of narratives about our personal (microsystem) and institutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…We found that this enabled us to feel confident and safe. Indeed, we agree with Pryer et al (2023) and colleagues’ assertion that it is the willingness to share evocative, vulnerable and rich experiences, which makes the collaborative autoethnographic method ‘incredibly useful for other lived experience researchers’ (p. 1541).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We found that this enabled us to feel confident and safe. Indeed, we agree with Pryer et al (2023) and colleagues’ assertion that it is the willingness to share evocative, vulnerable and rich experiences, which makes the collaborative autoethnographic method ‘incredibly useful for other lived experience researchers’ (p. 1541).…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, we concur with Pryer et al (2023) on the importance of a 'deep camaraderie and trust among [the] team' (Pryer et al, 2023(Pryer et al, : 1541. We found that this enabled us to feel confident and safe.…”
Section: In Addition To These Contributions We Find Implications For ...supporting
confidence: 79%
See 1 more Smart Citation